2018
DOI: 10.1186/s13014-018-1032-z
|View full text |Cite
|
Sign up to set email alerts
|

Automated VMAT planning for postoperative adjuvant treatment of advanced gastric cancer

Abstract: BackgroundPostoperative/adjuvant radiotherapy of advanced gastric cancer involves a large planning target volume (PTV) with multi-concave shapes which presents a challenge for volumetric modulated arc therapy (VMAT) planning. This study investigates the advantages of automated VMAT planning for this site compared to manual VMAT planning by expert planners.MethodsFor 20 gastric cancer patients in the postoperative/adjuvant setting, dual-arc VMAT plans were generated using fully automated multi-criterial treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Subsequently, the process has an intrinsic drive to beat the MANplan quality [12,13]. Many studies have demonstrated superiority of Erasmus-iCycle AUTOplans over MANplans generated with conventional trial-and-error planning [9,[14][15][16][17][18][19]. For clinical application at Erasmus MC, the system is used as a pre-optimizer for automated plan generation in the FDA-approved clinical TPS [9,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the process has an intrinsic drive to beat the MANplan quality [12,13]. Many studies have demonstrated superiority of Erasmus-iCycle AUTOplans over MANplans generated with conventional trial-and-error planning [9,[14][15][16][17][18][19]. For clinical application at Erasmus MC, the system is used as a pre-optimizer for automated plan generation in the FDA-approved clinical TPS [9,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…RT elds including or excluding the remnant stomach. Several studies have found that IMRT was superior to two-dimensional or three-dimensional RT, providing a more conformal and homogeneous dose to the PTV and accordingly minimizing the probability of toxicity [32][33][34].We had previously determined that tomotherapy is a better option for adjuvant treatment of gastric cancer due to its superior bowel and bone marrow dose sparing, dose conformity, and dose homogeneity [6,7,35,36]. Given these evidences, the present study showed acceptable safety and comparable compliance with the treatment course.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, RT planning is often a time consuming trial and error process, which is not reproducible and its success depends highly on the planner's experience. Automation of the planning process may overcome those problems and therefore automatic treatment planning gained attention in recent years [4][5][6][7][8][9][10]. In principle, three major conceptual approaches have been proposed for automatic RT planning in the last years.…”
Section: Introductionmentioning
confidence: 99%